1997
DOI: 10.3109/10428199709059685
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Impact of Light Chain Associated (AL) Amyloidosis on the Prognosis of Patients with Multiple Myeloma Treated with Autologous Transplantation

Abstract: Little is known about the incidence of clinically occult AL amyloid in patients with multiple myeloma and its impact on prognosis of these patients. To address these issues, subcutaneous fat pad aspirates (SAFA) and bone marrow biopsies were evaluated for the presence of amyloid in a cohort of newly diagnosed patients with multiple myeloma prior to enrollment on a phase II study including tandem transplants. Organ directed biopsies were performed when clinically indicated. Presence of amyloid at > or = 1 site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
12

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 12 publications
3
70
1
12
Order By: Relevance
“…Some authors found out MM-associated asymp-amyloid in up to 26% of patients at the time of diagnosis (8); this was also an independent high-risk prognostic factor for MM patients, thus suggesting need for searching amyloid and need for aggressive treatment. Others believe that AL deposits, even if not rare, are clinically inconsequential and should not influence MM therapy, so active screening is unnecessary (6,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors found out MM-associated asymp-amyloid in up to 26% of patients at the time of diagnosis (8); this was also an independent high-risk prognostic factor for MM patients, thus suggesting need for searching amyloid and need for aggressive treatment. Others believe that AL deposits, even if not rare, are clinically inconsequential and should not influence MM therapy, so active screening is unnecessary (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 puts our findings into the context of prior reports. One of the first reports addressing this question was by Desikan et al (6), who prospectively evaluated fat pad aspirate and BM biopsy for amyloid deposit in a cohort of 84 MM patients. Amyloid was detected in 38% of patients; fat pad aspirate was positive in 25% and BM in 10% of cases and other organ sites in 7 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports suggest that 10% to 15% of patients with MM may develop overt AL amyloidosis during the course of their disease, and up to 38% of patients with MM may have clinically occult AL amyloid deposits. 3,4 We designed the current study to iden tify and describe the clinical features, diagnosis, treatment patterns and response, and outcome among patients who were diagnosed as having AL amyloidosis subsequent to a diagnosis of MM. We describe 47 patients with a histologic diagnosis of AL amyloidosis, made at least 6 months after the initial diagnosis of MM, thus excluding patients with symp tomatic AL amyloidosis at the time of the diagnosis of MM.…”
Section: © 2010 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
“…A carpal tunnel tissue biopsy was positive in 6 patients (13%), and 1 patient had a positive biopsy from a gluteal mass. The diagnosis of AL amyloidosis was established by demonstrating amyloid in various target organs in 12 patients (26%) (lung [5], kidney [4], heart [1], small bowel [1], and liver [1]). Echocardiographic findings suggestive of amyloid cardiomyopathy, such as thick ened ventricular wall and/or interventricular septum, and diastolic dysfunction were observed in 15 patients (32%); corresponding restrictive changes were revealed by cardiac catheterization in 1 patient.…”
Section: Diagnosis Of Amyloidosismentioning
confidence: 99%